Penerapan Teknologi Barcode dalam Sistem Manajemen Surat untuk Peningkatan Otentikasi dan Efisiensi Dokumen (Journal Digital Technology Trend, 2024)
This study aims to implement and evaluate a barcode-based mail management system at the Biro Administrasi Pembangunan Setda Aceh. The findings indicate that the application of barcode technology in mail management significantly enhances the efficiency and security of administrative processes. After implementation, the number of mails processed daily increased by 30%, while the error rate in archiving decreased from 5% to less than 1%. Additionally, the time required for document approval reduced from 48 hours to less than 24 hours, boosting overall productivity. User satisfaction surveys revealed that 85% of users felt the system helped them complete tasks faster, and 90% felt more secure due to improved authentication and tracking features. Some user suggestions included the need for additional training and enhancements to the user interface. These results provide guidance for other organizations looking to adopt similar technologies to improve their document management.